Effect of estradiol benzoate injection to male rabbits on glucose, total protein, albumin, calcium concentrations and prostate tissue - Elkhier, Tamour; Hassaballa, Shams-Eldein; Omer, Shadia Abdo-Elatti; Adam, Abdelnasir (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: This study was carried out to investigate the effects of estradiol benzoate (EB) injection to male rabbits on glucose, total-protein, albumin, calcium concentrations and prostate tissue, and the role of prolactin as an important mediator of estrogen action in prostate. Materials and methods: Fifty four adult male rabbits were used in this study. The rabbits were randomly divided into two groups. Group A contained 36 male rabbits, which were further randomly divided into four sub-groups, three of them contained 10 rabbits and one sub-group contained 6 rabbits as control. Group B contained 18 male rabbits, which were divided randomly into three equal sub-groups. Three sub-groups of Groups A and B were treated once each on alternative day with the intramuscular injections of EB dosed at 40, 80 and 120 µg/rabbit, respectively for 20 days, whereas the fourth sub-group of Group A received no estradiol, and Group B received 1 mg Bromocriptine Mesilate in addition to EB through oral route on each alternative day. Blood samples were collected for measuring glucose, t-protein, albumin and calcium levels. Prostate tissue samples were collected from all the rabbits for histological studies. Results: Glucose was significantly (P?0.05) increased as a result of 80 µg EB injection, while significantly (P?0.05) decreased due to 40 and 120 µg EB injection. Total protein significantly (P?0.05) increased due to injection of 40 µg EB, however t-protein was not changed due to 40 and 120 µg injection. On the other hand, the results of albumin and calcium were not affected (P?0.05) by EB. In prostate tissues, EB induced hyperplasia with dysplasia or dysplasia only, but this effect was mild due to inhibition of prolactin. Conclusion: The injection of EB to male rabbits increased or decreased glucose level, increased t-protein level mildly or not changed, while albumin and calcium levels were not affected. EB induced hyperplasia on prostate tissue, and this effect was reduced by prolactin inhibition indicating that prolactin might have a role on the action of estrogen. http://doi.org/10.5455/javar.2017.d184